THE IMPORTANCE OF ESP IN TEACHING ENGLISH TO STUDENTS OF THE AGRICULTURAL SECTOR (INTERNATIONAL JOURNAL OF SCIENCE AND TECHNOLOGY, 2025)
The aim of this paper is to explore the significance of English for Specific Purposes (ESP) in teaching English to students in theagricultural sector. As globalization increases, the demand for specialized knowledge of English in various industries, includingagriculture, grows. ESP courses tailored to the needs of agriculture students play a vital role in preparing them for internationalcollaboration, research, and access to global resources. This paper outlines the key benefits of ESP in the agricultural sector anddiscusses effective teaching strategies.